Charge transfer of He2 + with H in a strong magnetic field*Project supported by the National Natural Science Foundation of China (Grants Nos. 11104017, 11025417, 11275029, and 11474032), the National Basic Research Programm of China (Grant No. 2013CB922200), and the Foundation for the Development of Science and Technology of the Chinese Academy of Engineering Physics (Grant Nos. 2014B09036 and 2013A0102005). (20th July 2015) - Liu 刘, Chun-Lei 春雷; Zou 邹, Shi-Yang 士阳; He 何, Bin 斌; Wang 王, Jian-Guo 建国
Abstract: By solving a time-dependent Schrödinger equation (TDSE), we studied the electron capture process in the He 2 + +H collision system under a strong magnetic field in a wide projectile energy range. The strong enhancement of the total charge transfer cross section is observed for the projectile energy below 2.0 keV/u. With the projectile energy increasing, the cross sections will reduce a little and then increase again, compared with those in the field-free case. The cross sections to the states with different magnetic quantum numbers are presented and analyzed where the influence due to Zeeman splitting is obviously found, especially in the low projectile energy region. The comparison with other models is made and the tendency of the cross section varying with the projectile energy is found closer to that from other close coupling models.